As avaliações em larga escala e sua relação com a qualidade da educação: caminhos percorridos por um Colégio de Aplicação Federal - Ribeiro, Andréa Porto (2023)
This doctoral research aimed to analyze the influence of large-scale assessments on the educational reality of a Federal Application School (CAp). Through the investigation, we aimed to gather elements that would help us to apprehend the influences of the macro context in a micro context, particularly considering the specificities of the teaching and learning processes in interfaces to the evaluation in the participating school. We seek to contribute to the deepening of reflections and propositions that are based on the results of standardized tests applied on a large scale to (re)think and build public education in our country. We believe that research on the subject constitutes an important framework to qualify the debate on the use of standardized tests as a public policy to address the quality or lack thereof in our schools. For that, we rely on the writings of Freitas (2010, 2012, 2018); Sordi (2009); Saul (2015), Almeida, Rios (2002), Bondioli (2012), Dourado, Oliveira e Santos (2007), Fernandes (2009), Afonso (2007, 2014, 2018) among others, on public education, quality and large-scale assessments. The on-screen research effort aligns with the qualitative approach as we seek to respond to our objectives in the context of the investigated phenomenon by adopting descriptive procedures for constructing and interpreting the data. In this sense, we analyzed theses and dissertations linked to Capes on the subject of large-scale evaluation and external evaluation. The search indicated a recurrence of works on the subject in the last decade, however, it showed the absence of research involving CAps and a reduced number of studies involving all school segments. The field work included different instruments for the construction of empirical data, the instruments were chosen considering their potential to provide the necessary material to achieve the objectives, as well as allowing the participation of all segments of the school community in a remote way, having In view of the period of social distancing caused by the Covid-19 health crisis, they are the questionnaire, the focus group (FG) and the semi-structured interview. Analysis of documents regarding the constitution of CAps in Brazil, the Pedagogical Political Project (PPP), legislation and others that were related to the participating school were also developed. The data obtained were organized according to the nature of each material guided by content analysis (BARDIN, 2009). The results showed that large-scale assessments have little influence on the participant CAp. The evaluation adopted by the school is in line with the formative perspective. In this way, educational actions are built with broader objectives in mind, in accordance with the unit's PPP. In our analyses, we identified the lack of consensus on the need for large-scale assessments, however institutional recognition of the existence of these tests remains. We observe, along these lines, that the quality of the school for the participants is not restricted to large-scale evaluation, because according to different segments, this type of evaluation is a partial picture of the reality experienced. The data indicate the presence of central and consensual elements about the quality of education that express a high qualitative level negotiated by the collective, which in our view are healthy elements for building schools with socially referenced quality. They involve the concrete working conditions of education professionals, such as social and financial valuation, career plan and training. As well as the need for an expanded, democratic and therefore participatory curriculum.